PENERAPAN METODE MENGAJAR YANG EFEKTIF DALAM PROSES PEMBELAJARAN DARING - Sheptian Krisyanto Petrus Hutasoit; Eni Rombe; Tantri Yulia (STT Kristus Alfa Omega, 2021)
Based on the results of temporary observations, the researchers found that the teaching method used by the STT Christ Alfa Omega lecturer was less effective, as evidenced by the lack of enthusiasm of students towards the material provided by the lecturer, this was based on interviews with several students. So the purpose of this research is to find out how big the level of application of effective teaching methods in the online learning process at STT Christ Alfa Omega is. The method used is descriptive quantitative method. Based on data analysis, the value of applying effective teaching methods in the online learning process at STT Christ Alfa Omega is in the high category or 88.49%.